Contribution to the knowledge of the mycophagous Coccinellini (Coleoptera: Coccinellidae) from the Cusco Department, Peru - Bustamante-Navarrete, Abdhiel Arnaldo (2021)
In this work, we presented a review of the specimens of mycophagous Coccinellini from various provinces of the Cusco Department, south east of Peru. This group currently has nine species in the country, within the genera Oxytella Weise 1902, and Psyllobora Chevrolat 1836. In the material examined the occurrence of five of them is reported: Oxytella longula Weise, Psyllobora marshalli Crotch, P. abancayana Almeida, P. constantini González, Perla & Almeida, and P. hybrida (Mulsant); in addition to three other species, not yet identified, within the genus Psyllobora. For each species a diagnosis, photographs and photomicrographs of habit and genital structures, and information on their distribution in Cusco are presented.